Nitzschia papillosa (Bacillariaceae, Bacillariophyta): a new species from a Brazilian salt marsh - Bertolli, Lucielle Merlym; Talgatti, Dávia Marciana; Torgan, Lezilda Carvalho (Phytotaxa, 2016)
A new species of the genus Nitzschia was found in epiphyton and microphytobenthos at the Patos Lagoon salt marsh (Rio Grande do Sul State, southern Brazil). Nitzschia papillosa sp. nov. was described under light and scanning electron microscopy and compared with other species from the section Lanceolatae. The species presents features shared by several species of the genus such as a linear-lanceolate outline, cuneate ends and irregularly distributed fibulae. The distinguishable feature is a row of dots on the margin opposite to the fibulae. In scanning electron microscopy, these structures appear as silica excrescences, little rounded or squared, which we refer as papillae, situated at the transapical costae in the internal valve face. This is the first record of this kind of ornamentation in Nitzschia species.